2007
DOI: 10.1088/0953-8984/19/19/196213
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing high-temperature spin dynamics in La1−xCaxMnO3from a mapping of EPR linewidth andg-factor

Abstract: We report the measurements of electron paramagnetic resonance (EPR) on powder samples of La 1-x Ca x MnO 3 at the commensurate carrier concentrations of x = N/8 (N = 1, 2, 3, 4, 5, 6, and 7) within temperature range 100K 450K T ≤ ≤. It is suggested that the mapping of EPR linewidth and g factor is a useful way to reveal the high-temperature spin dynamics in La 1-x Ca x MnO 3 . An electron-hole asymmetry can be clearly observed in the mapping of g factor. The linewidth ∆H as a function of x drops at x = 3/8 due… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 36 publications
0
24
0
Order By: Relevance
“…It can be seen that in bulk Er 2 O 3 , the EPR signal was not observed, while in Er 2 O 3 NPs, a EPR signal was detected in the range of 880–5580 Gauss with g factor about 1.9951. In general, when the actual measured g factor is lower than the free electron g factor (g free = 2.0023), the EPR signal represents the electron trap32. In other words, the EPR signal in Er 2 O 3 NPs is assigned to the oxygen defects.…”
Section: Results and Disscussionmentioning
confidence: 99%
“…It can be seen that in bulk Er 2 O 3 , the EPR signal was not observed, while in Er 2 O 3 NPs, a EPR signal was detected in the range of 880–5580 Gauss with g factor about 1.9951. In general, when the actual measured g factor is lower than the free electron g factor (g free = 2.0023), the EPR signal represents the electron trap32. In other words, the EPR signal in Er 2 O 3 NPs is assigned to the oxygen defects.…”
Section: Results and Disscussionmentioning
confidence: 99%
“…1C, D). In order to understand the nature of these resonance peaks and to accurately calculate corresponding intensities, linewidth and resonance fields, we have fitted the ESR signals by the following equation [33,34]-…”
mentioning
confidence: 99%
“…A possible reason for this invalid conclusion may be an inadequate method of PM g factor extraction used by the authors. Thus, it seems useful to comment on this and some other points of [1].…”
mentioning
confidence: 99%
“…Liu et al reported in their recent paper [1] data on electron paramagnetic resonance (EPR) measured for polycrystalline La 1−x Ca x MnO 3 (LCMO) manganites at the commensurate carrier concentrations of x = N/8 (N = 1, 2, 3, 4, 5, 6, and 7). Using numerical fittings of the EPR spectra (dP/dH ), where P is a microwave energy absorbed by the sample and H is an external magnetic field, they extracted the temperature (T ) and concentration dependences of the EPR signal linewidth H pp and g factor within the interval 100 K T 450 K. The temperature dependences of H pp and the EPR signal intensity (I ) were further discussed by the authors in the framework of known models [2][3][4][5][6] and they claimed, as a result of this analysis, that 'An electron-hole asymmetry can be clearly observed in the mapping of the g factor and linewidth H '.…”
mentioning
confidence: 99%